LITERATURE REVIEW : Pengaruh Aquatic Plyometric Training Terhadap Kelincahan Pada Pemain Basket - Intan Sukma Anggreani, (2020)
Agility is an important element of physical condition, especially in sports including basketball . This study aims to examine the literature, journals, articles or research results with the topic of the influence of aquatic plyometric training to agility in basket ball players. Method: Search for sources of literature, journals, articles, research results in several databases such as Google Schoolar, PubMed, Science Direct and Plos One by using certain keywords in the period 2012-2020. From the literature search results, 5 articles met the source inclusion criteria. The methodological quality assessment of 5 articles was assessed using the Scimago Journal & Country Rank (SJR). Analysis of 5 journals was carried out based on the suitability of the topic, the research methods used, subject, interventions, instruments/parameters, and the results of each article. Results: After reviewing the literature as many as 5 articles showed that Aquatic plyometric training cannot improve the agility a person . Conclusion: Aquatic plyometric training cannot significantly increase the agility for basketball players